The relationship between physical conditions of the house and the presence of people in the same house with the incidence of pulmonary TB In the Working Area of Putri Ayu Community Health Center, Jambi City in 2024 - Zulhayati; Dwi Noerjoedianto; Fajrina Hidayati; Ummi Kalsum; Helmi Suryani Nasution (International Journal of Health Engineering and Technology, 2025)
Background Behind: Tuberculosis (TB) is one of the 10 leading causes of death globally and is a contagious disease. Pulmonary tuberculosis is caused by Mycobacterium tuberculosis, which spreads when people... Which suffer tuberculosis lungs cough with ethics cough that no true so that other people can be infected through the droplets released. This study aims to determine the relationship between residential density, temperature, humidity, floor type, family income, Education level, smoking status, and presence of household contacts with incident Pulmonary TB in region Putri Ayu Community Health Center, Jambi City in 2024. Method: This type of research is quantitative research with a case control study design. Population in study This is all over Pulmonary TB sufferers Which is at in region Work Putri Community Health Center Ayu City Jambi. Sample in research This as much as 62. Technique sampling with use random example. Collection data using questionnaires and observations, univariate and bivariate data using the chi- square test. Results: There is an income relationship OR 0.238> 1(95% CI, 0.084 -0.677) and the presence of a box in the same house OR 68,200> 1 (95% CI, 8,129 -572,176) with the incidence of pulmonary TB. There is no relationship between residential density, temperature, humidity, floor type, education level, smoking status, Conclusion: Variables Which relate that is the emergence and presence of household contacts. Therefore, it is recommended to improve socioeconomic conditions and early detection of pulmonary TB.